2017
DOI: 10.1093/mnras/stx2983
|View full text |Cite
|
Sign up to set email alerts
|

Microquasars as heating sources of the intergalactic medium during reionization of the Universe

Abstract: The effect of the primeval sources of radiation and particles on the thermodynamical state of the intergalactic medium during the Epoch of Reionisation is still unclear. In this work, we explore the contribution of electrons accelerated in the jets of highredshift microquasars to heating and ionising the intergalactic medium. We develop Monte Carlo simulations of the propagation and energy deposition of these electrons as they travel away from their sources. We find that microquasars contribute significantly t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 90 publications
(129 reference statements)
0
18
0
3
Order By: Relevance
“…However, most recent works have focused on semi-numerical (see e.g. Santos et al 2010;Mesinger et al 2013;Fialkov et al 2014;Knevitt et al 2014;Ghara et al 2016Ghara et al , 2017Greig & Mesinger 2018;Das et al 2017;Douna et al 2018) and numerical (eg. Xu et al 2014;Ahn et al 2015a;Ross et al 2017) modeling.…”
Section: Introductionmentioning
confidence: 99%
“…However, most recent works have focused on semi-numerical (see e.g. Santos et al 2010;Mesinger et al 2013;Fialkov et al 2014;Knevitt et al 2014;Ghara et al 2016Ghara et al , 2017Greig & Mesinger 2018;Das et al 2017;Douna et al 2018) and numerical (eg. Xu et al 2014;Ahn et al 2015a;Ross et al 2017) modeling.…”
Section: Introductionmentioning
confidence: 99%
“…High Mass X-ray Binaries (HMXBs) are systems composed of a compact object (neutron star NS, or black hole BH) and a massive companion star. Observational results have shown that HMXBs are good tracers of the star formation rate (SFR) within their host galaxies (Grimm et al 2003, Mineo et al 2012, and might be important heating and ionizing sources in the early Universe (e.g., Justham & Schawinski 2012, Artale et al 2015, Douna et al 2018, Garratt-Simthson et al 2018. From a theoretical point of view, studying the population of HMXBs within galaxies is essential to understand their role in the aforementioned processes and the binary evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Following that work Tueros et al (2014) proposed that microquasar jets contribute to the reionization of the IGM at cosmic dawn. More recently, Douna et al (2018) by Monte Carlo simulations find that the contribution of microquasar jets to the heating of the IGM is of the same order of magnitude as that of cosmic rays from SNe.…”
Section: Hmxbs In the Heating And Reionization Epochs: X-raysmentioning
confidence: 99%